The Relationship Between Social Support and Life Satisfaction Among Elderly Nursing Home Residents in Tehran - Mohammad Babapour; Ghoncheh Raheb; Mostafa Eglima (Sālmand, 2014)
Objectives: The purpose of this study was to investigate the relationship between social support and life satisfaction in nursing home residents in Tehran.